2013
DOI: 10.1089/fpd.2012.1470
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis ofSalmonella,Campylobacter,Escherichia coli, andEnterococcusin Animal Feed Ingredients

Abstract: The presence and antimicrobial susceptibility of foodborne pathogens and indicator organisms in animal feed are not well understood. In this study, a total of 201 feed ingredient samples (animal byproducts, n=122; plant byproducts, n=79) were collected in 2002 and 2003 from representative rendering plants and the oilseed (or cereal grain) industry across the United States. The occurrence and antimicrobial susceptibility of four bacterial genera (Salmonella, Campylobacter, Escherichia coli, and Enterococcus) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 25 publications
7
39
2
Order By: Relevance
“…Although none of these top four serotypes were detected in the APPI-rendered animal meal samples, both Salmonella Montevideo and Infantis, the major Salmonella serotypes from the rendered animal meals identified in this study, could be a concern for human food safety, as both serotypes have been identified to be associated with animalderived food commodities (16). Similar findings were found by Ge et al (12) who analyzed a total 201 feed ingredient samples for Salmonella, Campylobacter, E. coli, and Enterococcus and reported the detection of both Salmonella serovars Montevideo and Infantis.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Although none of these top four serotypes were detected in the APPI-rendered animal meal samples, both Salmonella Montevideo and Infantis, the major Salmonella serotypes from the rendered animal meals identified in this study, could be a concern for human food safety, as both serotypes have been identified to be associated with animalderived food commodities (16). Similar findings were found by Ge et al (12) who analyzed a total 201 feed ingredient samples for Salmonella, Campylobacter, E. coli, and Enterococcus and reported the detection of both Salmonella serovars Montevideo and Infantis.…”
Section: Resultssupporting
confidence: 88%
“…Although human and animal gastrointestinal tracts are major reservoirs of antimicrobial resistant bacteria, the animal feeds may play an important role in supplying antibiotic-resistant bacteria to the animal, as a few studies reported the presence of antimicrobial-resistant bacteria, especially enterococci, in animal feeds, such as rendered animal by-products (7,12,14). However, according to the 2011 National Antimicrobial Resistance Monitoring System executive report, there was a continued decline of Salmonella resistance to antibiotics (23).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, salmonellapositive results were only in the samples obtained from feed factories. This finding was associated with secondary contamination sources such as transportation, factory staff and storage conditions and was not in accordance with Ge et al [23] . Although the revolutionary improvements in food safety have been occured during the last 50 years, still in existence of cross-contaminations in rendered animal products for poultry feed are questionable [24,25] .…”
Section: Discussioncontrasting
confidence: 65%
“…Pomeroy et al [22] collected 980 samples of animal feed products from 22 different states in USA and they isolated 43 Salmonella strains originated from secondary contaminations in 170 samples. In a recent study, a total of 201 feed ingredient samples (122 animal by-products and 79 plant by-products) were collected from rendering plants and oilseed industry and it eas reported that Salmonella were present in 22.9% of samples and animal by-products had a significantly higher Salmonella contamination rate (34.4%) than plant byproducts [23] . In our study, Salmonella serovars (Salmonella spp., Salmonella Enteritidis and Salmonella Typhimurium) were determined in 32 samples of 500 rendered animal products and source of agents were in accord with Watkins et al [21] and Pomeroy et al [22] .…”
Section: Discussionmentioning
confidence: 99%
“…While feed troughs have been reported as a source of VTEC cross-contamination on the farm (Shere et al, 1998;Van Donkersgoed et al, 2001), limited studies on VTEC in commercially produced feed as a source of the pathogen show its presence at very low levels, 0.2 % of feed components and 0.4 % of feed mill samples (Davies et al, 2003) or absent in feed ingredients (Ge et al, 2013) Transmission of VTEC O157:H7 and other VTEC serogroups can occur rapidly in groups of cohoused bovines on farms, in transport and in lairage, with cross-contamination from hides of cohort animals and the environment. The grooming behaviour of bovines plays an important role in the transmission of VTEC among co-housed animals (McGee et al, 2004).…”
Section: Risk and Risk-reducing Factorsmentioning
confidence: 99%